Study of the Comparative Activity of Piperacillin/Tazobactam with Currently Available Antibiotics against 8206 Aerobic Isolates - Kevin R Forward; Donald E Low; Michel Laverdiere; Robert Rennie; Andrew E Simor; Patricia A Franks; Members of the Canadian Piperacillin/Tazobactam Study Group (Canadian Journal of Infectious Diseases)
OBJECTIVES: To compare the activity of piperacillin-tazobactam with piperacillin and other parenterally administered antibiotics against aerobic Gram-negative bacilli and Gram-positive cocci isolated from across Canada, and to determine the prevalence of resistance mediated by extended-spectrum cephalosporinases.